Educational public policy during the pandemic: Comparative study of Mexico and Ecuador - Torres-Toukoumidis, Angel; González-Moreno, Sonia Esther; Pesántez-Avilés, Fernando; Cárdenas-Tapia, Juan; Valles-Baca, Herik Germán (Education Policy Analysis Archives, 2021)
The atypical situation produced by the Covid-19 pandemic has led governments to make decisions in the educational sector to solve with immediacy the contingencies produced by the health crisis. This study carries out a comparative-descriptive systematization between two countries, Ecuador and Mexico, analyzing 60 official documents based on four units of analysis connected to educational public policies: social competence, diagnosis, program, and proposed actions. The results show that, although there are common actions such as the suspension of classes and telework, virtual learning programs – “Aprende en Casa” Mexico and “Educación en Casa” Ecuador – there are also contrasts. Among these, it is evident that education policy decision-making in Ecuador is more decentralized than in Mexico, and that social competencies in Ecuador are oriented to administrative staff, students, families and teachers, while in Mexico, in addition to those mentioned, these also include media and government employees of the Ministry of Public Education. These findings confirm that the operationalization of the legislative framework issued during this emergency in the educational field will provide lessons for the return to post-pandemic activities.